The defender's vision-gaze behavior of one-on-one defenders in basketball - Meyer, J.; Fasold, F.; Schul, K.; Sonnenschein, M.; Klatt, S. (Journal of Sport & Exercise Psychology, 2022)
In fast-paced team sports, anticipation is one important element in defense strategies. The primary objective of this study was to examine the recommendation for action and use of defensive gaze strategies by defensive players in basketball. Four national-level expert-basketball coaches were interviewed and a field study with mobile eye-tracking devices was conducted on 16 expert and 16 novice players defending in a one-on-one situation. Differences in relative fixation times between experts and novices were elaborated for the predetermined gaze zones—head, ball, torso, and feet—as given by the expert coaches. This was done for three phases of the movement sequence: receiving, dribbling, and shooting. The results of the interviews with expert coaches indicated that the existing coaching doctrine instructs players to look at the torso of an opponent to avoid being vulnerable to fakes. Surprisingly, our findings with the players showed a discrepancy in the evaluated gaze behavior of the experts and novices. For the receiving and dribbling phase, experts mainly fixated their gaze on the head while novices focused on the ball. For the final shooting phase, both the groups mainly fixated their gaze on the ball. Fixating the gaze on the ball or head makes the player potentially vulnerable to deceptive movements, as video-based research has shown. Expert coaches also indicated that peripheral vision is of importance to defenders, contradicting the existing assumption in the literature that focusing on the task-relevant areas is key for anticipation performance.